Assessing barriers to insulin therapy among people with type 2 diabetes in South Africa using the Insulin Treatment Appraisal Scale: A cross-sectional survey. Issue 4 (August 2022) - Ngassa Piotie, Patrick; Muchiri, Jane W.; Webb, Elizabeth M.; Rheeder, Paul
Abstract: Aims: To assess barriers to insulin therapy among people with type 2 diabetes after adapting the Insulin Treatment Appraisal Scale (ITAS) to the South African context. Methods: A panel of experts reviewed the original ITAS for clarity and relevance to the South African context. The ITAS was administered to 253 adults with type 2 diabetes attending diabetes outpatient clinics in the Tshwane Metropolitan Municipality. Internal consistency (Cronbach's alpha) was tested and construct validity was examined using exploratory factor analysis (EFA). PIR was appraised in insulin users and non-users. Results: The EFA revealed that the adapted ITAS had a two-factor structure, similar to the original scale, with acceptable internal consistency (α = 0.85). Insulin-using participants had significantly less negative attitudes to insulin therapy than non-users (40.7 ± 7.1 vs. 51.5 ± 11.2, p < 0.001). Compared to participants who used insulin, participants who did not use insulin were afraid of injecting themselves with a needle (71% vs. 11%, p < 0.001) and saw insulin treatment as a sign of worsening diabetes (63% vs. 29%, p < 0.001). Conclusions: Consistent with previous studies, participants who were not using insulin had more negative beliefs and attitudes towards insulin treatment than those who were already using insulin. South African clinicians should use the ITAS to assess positive and negative perceptions regarding insulin therapy in both insulin-naïve and insulin-treated people, to evaluate interventions to reduce PIR and improve treatment outcomes. Highlights: The Insulin Appraisal Treatment Scale (ITAS) has not been used to assess barriers to insulin therapy in South Africans living with diabetes. An expert panel found that the ITAS is relevant to the South African context. Insulin-naïve participants held more negative beliefs towards insulin than those who were on insulin. The negative attitudes of non-insulin users were related to injection-related anxieties including fear of injection and pain.